Impact Assessment of Brazil's International Tourism Promotion Policy - Vieira, Daniel Pires; Teixeira, Edmércia; da Silva Neto, Pedro (Anais Brasileiros de Estudos Turísticos, 2022)
The use of public policy assessment to improve government action is an urgent need, but the practice is still in its infancy in Brazil. This article aims to contribute to the discussions on public policy evaluation in Brazil by establishing a method and evaluating the results of the Brazilian international tourism promotion policy. For this purpose, data were collected on investments made by Embratur in priority markets between 2014 and 2017. To assess the impact of investments, information was collected on the number of tourists received and on tourists´ average daily expenditure per capita. Data were analyzed using descriptive statistics and panel data regression analysis. The results show the absence of statistical significance on the relationship between investments and tourist expenditure. Considering the tourist flow, investments presented a significant and positive result, but only for short-distance markets. The evidence found allows us to assess and guide Brazilian international tourism promotion policy.